2018
DOI: 10.5812/ijem.65078
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Human Development Index and Its Components with Thyroid Cancer Incidence and Mortality: Using the Decomposition Approach

Abstract: BackgroundThe link between age specific-rates of thyroid cancer (TC) and human development index (HDI) and also its components can be a new direction for planning by policy makers.ObjectivesThis study aimed at identifying the relationship between TC rates by gender, and HDI and its components in different regions of the world.MethodsAn ecological study was conducted; the data was obtained from the GLOBOCAN project in 2012. Inequality in TC estimates (age-specific incidence and mortality rates), according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(32 reference statements)
3
9
0
Order By: Relevance
“…This study clearly itemizes the socio-demographic, clinical, histological and immunohistochemistry characteristics of the Nigerian breast cancer patients in a hospital-based study. In this study, the mean age was 46 years with majority of women aged between 41 and 50 years, similar to the findings in previous studies in Nigeria but in contrast to western countries where most of the breast cancer patients are postmenopausal [5,20]. Some studies have postulated a decrease in levels of circulating estrogen levels as responsible for the decreasing age of breast cancer patients worldwide [21,22].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study clearly itemizes the socio-demographic, clinical, histological and immunohistochemistry characteristics of the Nigerian breast cancer patients in a hospital-based study. In this study, the mean age was 46 years with majority of women aged between 41 and 50 years, similar to the findings in previous studies in Nigeria but in contrast to western countries where most of the breast cancer patients are postmenopausal [5,20]. Some studies have postulated a decrease in levels of circulating estrogen levels as responsible for the decreasing age of breast cancer patients worldwide [21,22].…”
Section: Discussionsupporting
confidence: 87%
“…The HDI is defined as the average achievement of three factors, including life expectancy at birth, gross national income per capita, and mean and expected years of schooling. Low HDI level includes countries that are the least developed and the very high HDI level includes the most developed countries [5]. Although, low human development index countries (L-HDI) like Nigeria have a lower incidence of breast cancer when compared to high human development index (H-HDI) countries like the United States of America (USA), mortality rates are higher [6].…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 26 , 27 Similar to our study, other investigations have shown comparable differences in mortality between genders as well. 28 One ecological worldwide study in particular demonstrated that the mortality rate in females was 2.5 times higher than males and corroborated the female gender as a risk factor for thyroid cancer. 28 , 29 However, it is important to note that these studies assessed thyroid cancer in general rather than specifically analyzing mortality rates among gender stratified by tumor grade.…”
Section: Discussionmentioning
confidence: 83%
“…24,26,27 Similar to our study, other investigations have shown comparable differences in mortality between genders as well. 28 One ecological worldwide study in particular demonstrated that the mortality rate in females was 2.5 times higher than males and corroborated the female gender as a risk factor for thyroid cancer. 28,29 However, it is important to note that these studies assessed thyroid cancer in general rather than specifically analyzing mortality rates among gender stratified by tumor grade.…”
mentioning
confidence: 83%